2013
DOI: 10.1016/j.crohns.2012.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical status, psychosocial impairments, medical treatment and health care costs for patients with inflammatory bowel disease (IBD) in Germany: An online IBD registry

Abstract: The registry constitutes a large complemental database for the patient population in Germany. About one third of the IBD patients were not in clinical remission (CDAI ≥150/CAI >4) (CD: 45%; UC: 27%), although high rates of immunosuppressive drugs (CD: 47%; UC 26%) were administered. This study shows a large burden of active disease associated with an unexpectedly high (co)morbidity and high psychosocial impairments, indicating a reduced health state in IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
56
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 27 publications
6
56
1
4
Order By: Relevance
“…Especially, relapses are associated with high health care costs and a decreased quality of life. [1][2][3] Up to 10% of IBD flares are reported to be the result of microbial pathogen invasion. 4 In the last decade, several studies have focused on the possible association between Clostridium difficile and IBD.…”
mentioning
confidence: 99%
“…Especially, relapses are associated with high health care costs and a decreased quality of life. [1][2][3] Up to 10% of IBD flares are reported to be the result of microbial pathogen invasion. 4 In the last decade, several studies have focused on the possible association between Clostridium difficile and IBD.…”
mentioning
confidence: 99%
“…5 Worryingly, nowadays this remains an issue, since a significant proportion of patients report lack of intimate relationships due to IBD and sexual problems seem to be common [20.6%]. 2,6 Despite the apparent impact of the impaired sexual function, the number of relevant studies is limited. Therefore, the aim of this study was to present the available data over the past 10 years concerning the evaluation of sexual function among males and females with IBD.…”
mentioning
confidence: 99%
“…2,3,4 Almost 40 years ago Gazzard et al reported a decreased sexual activity among patients with IBD. 5 Worryingly, nowadays this remains an issue, since a significant proportion of patients report lack of intimate relationships due to IBD and sexual problems seem to be common [20.6%].…”
mentioning
confidence: 99%
“…Several studies have concluded that anxiety and depression are common in IBD patients, and their severity parallels the disease activity [167][168][169][170]. These psychological conditions may not simply be the consequences of the chronic illness.…”
Section: Stress and Mood Disordersmentioning
confidence: 99%